BS EN 1455-1. Plastics piping systems for soil and waste discharge (low and high temperature) within the building structure. Acrylonitrile-butadiene-styrene (ABS). Part 1. Requirements for pipes, fittings and the system (20th July 2020) - British Standards Institution,
No abstract available